Analisis Kebijakan Pemulihan Eknomi Sektor UMKM Pasca Pandemi Covid-19 di Kota Pangkalpinang - Mayasari, Dessy (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The Covid-19 pandemic that has occurred for the past two years has in fact harmed the sustainability of economic activities, especially for the MSME sector in Indonesia. This impact is also felt by MSMEs in Pangkalpinang City who experience various very complex problems. This research was conducted as an effort to analyze the various problems that occurred as a result of the Covid-19 pandemic in the MSME sector and possible recovery strategies. The research method used in this study is the Quantitative Strategic Planning Matrix (QSPM) method. This QSPM is an in-depth analysis of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Based on the analysis of the two methods, it is obtained that the weighted IFE value is 2.350 and the weighted EFE value is 2.756. This shows that, the impact caused by the Pandemic on the MSME sector with several business recovery policies in the MSME sector in Pangkalpinang City, has had a pretty good effect because during the pandemic there was a decrease in production and distribution during the Covid-19 Pandemic, then these conditions gradually improved with alternative programs. Meanwhile, the results of the Quantitative Strategic Planning Matrix (QSPM) study show that the main strategy that must be developed more intensively by the Pangkalpinang City government is to encourage promotions using digital marketing concepts such as building market place platforms, strengthening branding and increasing access to capital for MSMEs in Pangkalpinang City.